Records of the Australian Music Centre - Australian Music Centre (1800)
MS Acc13.099 comprises papers relating to the composer Robert Watson Hughes (4 boxes).
Manuscript reference number: MS Acc13.099.
The Australian Music Centre (AMC) is a not-for-profit national service organisation dedicated to the promotion and support of both the artform of music and the creators and performers of contemporary classical, improvised jazz, experimental music and sound art in Australia.
Keywords: Hughes, Robert, -- 1912-2007.; Australian Music Centre -- Archives; Music -- Societies, etc. -- Archives; Composers -- Australia; Music -- Australia -- 20th century; Composers